Generation And Characterization Of Rna Aptamer Against Dengue Virus 2 Ns1 Glycoprotein - Sivalingam, Rogini (2018)
Dengue Fever, a mosquito borne viral disease, is a malady that plagues tropical and subtropical regions. A recent survey by WHO indicated, 3.9 billion of people in approximately 128 countries are at risk of infection with dengue viruses. The current predicament necessitates an ideal dengue diagnostic test, an assay that is able to distinguish dengue fever from other clinically similar diseases, highly sensitive, rapid and cost-effective. Antigen NS1 represents the potential diagnostic target of dengue as it was found to induce strong humoral response and is present at high concentrations in the blood up to 9 days after primary and secondary infections. However, the current diagnostic of dengue based on antibodies suffers from several drawbacks. Aptamers, ssDNA or RNA that have high affinity and specificity against the target, constitute a class of biomolecules that having the potential to alleviate the disadvantages of antibodies. This study endeavors to isolate RNA aptamer that have high affinity and specificity against NS1 of DENV 2, which is the most common serotype of dengue. A total of 11 SELEX cycles were carried out, whereby the eventual nucleic acid pool exhibited binding against the target NS1. Sequencing of the RNA pool revealed the presence of seven classes of sequences (named DENVI 1 to DENVI 7). DENVI 1, 3, 4, and 5 have the highest frequency of appearance with the percentage of 14.3%. DENVI 2 and DENVI 6 have the frequency of 7.1%, while DENVI 7 has the lowest frequency of 3.6%. Nitrocellulose filter binding assay has estimated binding affinity of 4.69±1 nM, 16.6±1 nM and 6.305±1 nM for DENVI 3, DENVI 4 and DENVI 6 aptamers, respectively.